2016
DOI: 10.3847/1538-4357/834/1/14
|View full text |Cite
|
Sign up to set email alerts
|

Giant Coronal Loops Dominate the Quiescent X-Ray Emission in Rapidly Rotating M Stars

Abstract: Observations indicate that magnetic fields in rapidly rotating stars are very strong, on both small and large scales. What is the nature of the resulting corona? Here we seek to shed some light on this question. We use the results of an anelastic dynamo simulation of a rapidly rotating fully-convective M-star to drive a physics-based model for the stellar corona. We find that due to the several kilo Gauss large-scale magnetic fields at high latitudes, the corona and its X-ray emission are dominated by star-siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
(51 reference statements)
2
13
0
Order By: Relevance
“…Likewise, stellar wind simulations have shown that stronger large-scale fields lead to higher mass loss rates (c.f., Garraffo et al 2015b, Pognan et al 2018, and more dense coronae (c.f. Cohen et al 2014Cohen et al , 2017. It is expected then that escaping CMEs under those conditions would sweep up more mass than in a weaker large-scale field case.…”
Section: Cme Massesmentioning
confidence: 98%
“…Likewise, stellar wind simulations have shown that stronger large-scale fields lead to higher mass loss rates (c.f., Garraffo et al 2015b, Pognan et al 2018, and more dense coronae (c.f. Cohen et al 2014Cohen et al , 2017. It is expected then that escaping CMEs under those conditions would sweep up more mass than in a weaker large-scale field case.…”
Section: Cme Massesmentioning
confidence: 98%
“…- Cohen et al (2017) perform magnetohydrodynamic calculations for a rapidly rotating, fully convective M star. Their simulations use a rotating spherical shell as a surrogate for a convection zone, generating both complex small-scale and dipole large-scale magnetic fields, combined with the Alfvén wave turbulence to mimic coronal heating.…”
Section: Applicability Of the Solar Single Loop Modelmentioning
confidence: 99%
“…PMS stars on the Hayashi track are fully convective and, even when slowed by star-disk coupling, rapidly rotating. It is widely believed that such stars generate magnetic fields through distributed turbulent α 2 -type magnetic dynamos rather than tachoclinal αΩ-type dynamos (Durney et al 1993;Yadav et al 2015;Cohen et al 2017;Warnecke & Käpylä 2020). Some calculations suggest that surface magnetic fields may be concentrated in high-latitude areas, but Zeeman effect observations of individual PMS stars indicate that complex multi-polar surface magnetic field configurations are typical (Gregory et al 2010).…”
Section: Applicability Of the Solar Single Loop Modelmentioning
confidence: 99%
“…This dynamo model not only has been tailored to match the mass, radius, and rotation period of Proxima Centauri (hereafter, Prox Cen), but also yields a long-term cyclic magnetic field evolution that roughly captures the observed time-scale of the activity cycle in this star (P cyc ∼ 7 years, see Suárez Mascareño et al 2016, Wargelin et al 2017. Cohen et al (2017) followed a similar approach to study the coronal structure of rapidly-rotating M-dwarf stars.…”
Section: Stellar Magnetic Fieldmentioning
confidence: 99%